The global contributions of working equids to sustainable agriculture and livelihoods in Agenda 2030 - Grace, Delia; Diall, O.; Saville, K.; Warboys, D.; Ward, P.; Wild, I.; Perry, Brian D. (Springer, 2022)
Small farmers produce most food in low- and middle-income countries and most small farmers rely on directly or indirectly working equids (WE). The lack of methods and metrics for assessing the role of WE hampers realisation of WE contributions. Based on literature review and a survey of WE welfare experts, we propose a framework for optimising WE potential based on two axes of sustainable development goals (SDGs) and value chains. WE contribute especially to earning and sparing income (largely in food production) (SDG 1), but also have roles in accessing health and hygiene services and products (SDG 3 and 5), providing edible products (SDG 2), and benefiting women (SDG 6), with lesser contributions to other SDGs, notably climate action (SDG 13). Experts identified barriers to appropriate appreciation of WE contributions, in order to target actions to overcome them. They found WE are neglected because they belong to farmers who are themselves neglected; because information on WE is inadequate; and, because the unique nature and roles of WE means systems, policies, investors, markets and service providers struggle to cater for them. Harnessing WE to optimally contribute to sustainable development will require generating better evidence on their contributions to SDGs, ensuring better integration into ongoing efforts to attain SDGs, and building the WE capacity among development actors.